OPTIMALISASI LAHAN PEKARANGAN KELUARGA MELALUI SINERGI PROGRAM P2B DAN KEMANDIRIAN PANGAN DI KOTA PROBOLINGGO - Siti Munifah; Amalia Juniarti (Program Studi Manajemen FEB UNM, 2026)
Efforts to achieve national food self-sufficiency can begin by strengthening food security at the household level through the Nutritious Food Yard (P2B) program. This community service activity aims to optimize residential yards in Probolinggo City through synergy between academia, government, and the community. The method employed is a participatory approach involving a